Aesthetic Education Camp: Benefits for Artists, Teachers, and Presenters - Beaudry, Marie-Christine (Canadian Review of Art Education / Revue canadienne d'éducation artistique, 2024)
For five years, Montreal’s Place des Arts has offered an aesthetic education camp in Montreal, in partnership with New York’s Lincoln Center Education, for artists, teachers, and presenters to support their cultural mediation efforts with students. This article reports on a study conducted on this innovative initiative. The results attest to the positive repercussions for the professional practices of the participants. Training in multidisciplinary teams led to the development of a shared vocabulary and the emergence of a community of practice. The findings indicate that cultural initiatives can have a positive impact on both cultural workers and those in education.